2021
DOI: 10.3389/fpsyg.2021.714641
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interoceptive Attention and Appraisal in Interoceptive Regulation

Abstract: Interoception, i.e., the processing and integration of sensory information has gained research interest due to its relevance in the psychopathological context. In the present review, we focus upon interoceptive regulation or one’s capacity to match bodily signals to his/her desired state by altering the signal or the desired state. More specifically, we discuss attention toward and appraisal of interoceptive stimuli as regulatory mechanisms of interoception. We review findings in the emerging research area of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…For the ERP analysis of the SRepRN and for each RepRN, 0.2 s and 0.05 s to sound onset, were respectively used as a baseline. (5) In order to have a standard against which to compare the activity evoked by the noise repetitions, analog epochs to (3) and (4) were obtained from trials with plain white noise. This was carried out avoiding EEG data matching AmN presentation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the ERP analysis of the SRepRN and for each RepRN, 0.2 s and 0.05 s to sound onset, were respectively used as a baseline. (5) In order to have a standard against which to compare the activity evoked by the noise repetitions, analog epochs to (3) and (4) were obtained from trials with plain white noise. This was carried out avoiding EEG data matching AmN presentation.…”
Section: Methodsmentioning
confidence: 99%
“…The brain continuously monitors the bodily and environmental signals, and the interplay between interoception and exteroception determines whether a change in state comes from within or from outside, triggering and shaping appropriate allostatic and behavioral responses (1-3). Although visceral signals are typically diffuse and not accessible to our conscious experience, interoception is considered to have a decisive role in perception, homeostatic responses, and motivational behaviors (4)(5)(6)(7). Recent research has demonstrated that bodily rhythms contribute to general brain dynamics impacting the processing of external information (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a conscious focus and awareness of bodily sensations is defined as interoceptive attention (Joshi et al, 2021). Several emotion theories (Barrett, 2009; Barrett & Russell, 2015; James,1884) propose that the perception of bodily reactions is a crucial component of the experience of emotion.…”
Section: Aging and Emotion Regulation: Lab And Everyday Lifementioning
confidence: 99%
“…There are clear theoretical parallels between the topics of interoception and mindfulness: traditional and contemporary methods for cultivating mindfulness are centred on the noticing of body sensations [ 3 , 6 , 7 , 8 ], and there are several interoceptive mechanisms that may impact mindfulness-based interventions, including interoceptive attention, interoceptive appraisal, and the use of interoceptive regulation strategies [ 9 ]. Reciprocally, interoceptive processing may be modulated through mindfulness-based training programmes via sustained attention to respiratory signals and bodily sensations such as pressure, movement and temperature, and cognitive and affective qualities of mindful attention to the internal body [ 8 ].…”
Section: Introductionmentioning
confidence: 99%